THEME EQUIVALENCE AND THEME SHIFT FOUND IN INDONESIAN-ENGLISH TRANSLATION OF THESIS ABSTRACTS - Damayanti, Yuanita (Universitas Negeri Semarang, 2012)
This study analyzes types of themes, theme equivalence, theme shifts in the Indonesian-English translation of thesis abstracts. The data consist of 10 thesis abstracts and their translation into English, taken from Postgraduate Program of Semarang State University from the last two years (2010-2011). The result shows that topical theme dominates the entire texts at 80.16% (198 out of 247) in ST and 79.56% (222 out of 279) in TT. Interpersonal theme is not found both in ST and TT. Most topical themes are in participants, followed by circumstance and process. The textual theme in both texts is adjunct conjunctive. Most of the themes (70.2%) are considered as non shift or equivalent. The theme shift occurrs through three processes: (1) by changing the grammatical function within the theme (11.7%), (2) by adding more themes (14.7%) and (3) by deleting themes (3.4%). It is suggested for a translator to have complete mastery over the grammatical structure of both the SL and TL and also being aware of the notions and application of shifts and equivalence.